Interrelations of slenderness ratio and main design criteria in supertall buildings - Ilgın, Hüseyin Emre (International Journal of Building Pathology and Adaptation, 2023)
PurposeTo date, there are no studies in the literature that provide a comprehensive understanding of the interrelationships between the slenderness ratio and the main design criteria in supertall towers (=300 m). In this paper, this important issue was explored using detailed data collected from 75 cases.Design/methodology/approachThis paper was carried out with a comprehensive literature review including the database of the Council on Tall Buildings and Urban Habitat(CTBUH) (CTBUH, 2022), peer-reviewed journals, MSc theses and PhD dissertations, conference proceedings, fact sheets, architectural and structural magazines and other Internet sources. In this study, the case study method was also used to gather and consolidate information about supertall towers to analyze the interrelationships. Cases were 75 supertall buildings in various countries [44 from Asia (37 from China), 16 from the Middle East (6 from Dubai, the United Arab Emirates), 11 from the United States of America and 3 from Russia, 1 from the UK].FindingsThe paper's findings highlighted as follows: (1) for buildings in the height range of 300–399 m, the slenderness ratio was usually between 7 and 7.9 and megatall towers were frequently built at a slenderness ratio of 10–15; (2) the median slenderness ratio of buildings in the 400–599 m height ranges was around 8.6; (3) a trend towards supertall slender buildings (=8) was observed in Asia, the Middle East and North America; (4) residential, office and mixed-use towers had a median slenderness ratio of over 7.5; (5) all building forms were utilized in the construction of slender towers (>8); (6) the medium slenderness ratio was around 8 for supertall buildings constructed with outriggered frame and tube systems; (7) especially concrete towers reached values pushing the limits of slenderness (>10) and (8) since the number of some supertall building groups (e.g. steel towers) was not sufficient, establishing a scientific relationship between aspect ratio and related design criteria was not possible.Originality/valueTo date, there are no studies in the literature that provide a comprehensive understanding of the interrelationships between the slenderness ratio and the main design criteria in supertall towers (=300 m). This important issue was explored using detailed data collected from 75 cases.